Scaling Relations of Early-Type Galaxies in MOND - Robin Eappen; Pavel Kroupa (Galaxies)
We investigate the shape and morphology of early-type galaxies (ETGs) within the framework of Modified Newtonian Dynamics (MOND). Building on our previous studies, which demonstrated that the monolithic collapse of primordial gas clouds in MOND produces galaxies (noted throughout as ‘model relics’ in the context of this work) with short star formation timescales and a downsizing effect as observationally found, we present new analyses on the resulting structural and morphological properties of these systems. Initially, the monolithically formed galaxies display disk-like structures. In this study, we further analyze the transformations that occur when these galaxies merge, observing that the resulting systems (noted throughout as ‘merged galaxies’ in the context of this work) take on elliptical-like shapes, with the <semantics>(Vrot/Vσ)</semantics>–ellipticity relations closely matching observational data across various projections. We extend this analysis by examining the isophotal shapes and rotational parameter <semantics>(λR)</semantics> of both individual relics and merged galaxies. The results indicate that ETGs may originate in pairs in dense environments, with mergers subsequently producing elliptical structures that align well with the observed kinematic and morphological characteristics. Finally, we compare both the model relics and merged galaxies with the fundamental plane and Kormendy relation of observed ETGs, finding close agreement. Together, these findings suggest that MOND provides a viable physical framework for the rapid formation and morphological evolution of ETGs.